Studies in Health Technology and Informatics Volume 14 - Case - Based Telematic Systems towards Equity in Health Care - France, F. H. Roger (IOS Press, 2014)
There are major disparities in health and in opportunities for promoting health between and within countries. As stated in the introductory paper of the WHO-EUR session : "the stability and coherence of the whole European region is threatened if conditions deteriorate too far in some countries in relation to others. Within countries, we all pay the price of letting injustice continue. If the most disadvantaged in society are left to carry the heaviest burden, then increases in crime, in insecurity and in violence are seen for everyone".